Comparison between al-Kafrawi’s Commentary on al-Ajurrumiyyah and al- Fawakih al-Janiyyah and Their Impact on the Teaching of Arabic Grammar - Maulidi, Toyyib (Universitas Al-Amien Prenduan, 2025)
Arabic grammar (nahwu) remains central to Islamic scholarship, yet the challenge of integrating its classical commentaries into modern pedagogical frameworks persists. This study offers a comparative analysis of Shar? al-Kafraw? ?al? al-Ajurr?miyyah and al- Faw?kih al-J?niyyah ?al? Mutammimah al-Ajurr?miyyah, two seminal works that have shaped grammatical instruction for centuries. Although grounded in the same linguistic tradition, the two texts differ significantly in structure, explanatory style, and pedagogical orientation. This research examines how these differences can inform contemporary nahwu education by revealing the distinct cognitive roles each commentary plays. Using a qualitative, library-based comparative method, the study shows that Shar? al-Kafraw? provides foundational clarity suitable for early-stage learning, while al-Faw?kih al- J?niyyah promotes analytical depth and reflective reasoning. The findings further demonstrate that integrating both commentaries creates a balanced dual-phase instructional model that aligns naturally with modern educational frameworks such as Higher-Order Thinking Skills (HOTS). The added value of this study lies in reframing classical texts as structured cognitive systems rather than merely historical references, highlighting their continued relevance for curriculum innovation—especially when enhanced through digital platforms such as the NIBS Center. Ultimately, this research asserts that classical nahwu commentaries remain pedagogically strategic tools capable of bridging traditional linguistic precision with the cognitive demands of 21st-century learning.